2010
DOI: 10.1177/1049909110373508
|View full text |Cite
|
Sign up to set email alerts
|

Morphine to Methadone Conversion: An Interpretation of Published Data

Abstract: For the past 20 years, methadone has been experiencing resurgence in the palliative care community as a second-line opioid for the treatment of cancer pain. The advantages of using methadone for refractory pain in patients with cancer or in those who could not tolerate the side effects of other opioids such as morphine are well cited in recent literature. Advantages of methadone over other opioids include dual elimination without active metabolites, allowing safe use with renal and liver failure, N-methyl-D-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…29 The AL method has been recommended on the basis of expert opinion, 31 but there is currently no consensus, based on empirical research, as to what is the safest and most effective method for rotation to methadone from other strong opioids. 32,33 The objectives of this review were to define the available evidence with regard to methods of rotation to methadone and to determine if sufficient evidence exists regarding the superiority (effectiveness and safety) of one method over others.…”
Section: Introductionmentioning
confidence: 99%
“…29 The AL method has been recommended on the basis of expert opinion, 31 but there is currently no consensus, based on empirical research, as to what is the safest and most effective method for rotation to methadone from other strong opioids. 32,33 The objectives of this review were to define the available evidence with regard to methods of rotation to methadone and to determine if sufficient evidence exists regarding the superiority (effectiveness and safety) of one method over others.…”
Section: Introductionmentioning
confidence: 99%
“…Proposed equianalgesic dose ratios for conversion of other opioids (in mg morphine equivalents) to methadone are variable and range from 3:1 to 10:1 at lower doses to 8:1 to 20:1 at higher doses. 78 In patients on lower doses of other opioids (eg, <40-60 mg morphine equivalents/ d), the panel suggests starting methadone at doses similar to those recommended for opioid-na€ ıve patients. For patients on higher doses of other opioids, the panel suggests that clinicians start methadone at a dose 75 to 90% less than the calculated equianalgesic dose, based on more conservative dosing ratios (eg, 15:1 to 20:1) and at no higher than 30 to 40 mg/ d.…”
Section: Initiation Of Methadonementioning
confidence: 99%
“…Opioid prescription dosages were converted into morphine equivalent dosages 28 . Equianalgesic dose ratios for conversion of methadone to morphine are variable depending on the dose of methadone or morphine 29 , and therefore in this study we also reported methadone equivalents. Receipt of COT was defined as receiving prescriptions for opioids for ≥90 consecutive days.…”
Section: Methodsmentioning
confidence: 99%